Viable SARS-CoV-2 Delta variant detected in aerosols in a residential setting with a self-isolating college student with COVID-19. (September 2022) - Vass, William B.; Lednicky, John A.; Shankar, Sripriya Nannu; Fan, Z. Hugh; Eiguren-Fernandez, Arantzazu; Wu, Chang-Yu
Abstract: The B.1.617.2 (Delta) variant of SARS-CoV-2 emerged in India in October of 2020 and spread widely to over 145 countries, comprising over 99% of genome sequence-confirmed virus in COVID-19 cases of the United States (US) by September 2021. The rise in COVID-19 cases due to the Delta variant coincided with a return to in-person school attendance, straining COVID-19 mitigation plans implemented by educational institutions. Some plans required sick students to self-isolate off-campus, resulting in an unintended consequence: exposure of co-inhabitants of dwellings used by the sick person during isolation. We assessed air and surface samples collected from the bedroom of a self-isolating university student with mild COVID-19 for the presence of SARS-CoV-2. That virus' RNA was detected by real-time reverse-transcription quantitative polymerase chain reaction (rRT-qPCR) in air samples from both an isolation bedroom and a distal, non-isolation room of the same dwelling. SARS-CoV-2 was detected and viable virus was isolated in cell cultures from aerosol samples as well as from the surface of a mobile phone. Genomic sequencing revealed that the virus was a Delta variant SARS-CoV-2 strain. Taken together, the results of this work confirm the presence of viable SARS-CoV-2 within a residential living space of a person with COVID-19 and show potential for transportation of virus-laden aerosols beyond a designated isolation suite to other areas of a single-family home. Highlights: Viable Delta Variant SARS-CoV-2 collected from air samples in a residential environment. SARS-CoV-2 detected in an area of a single-family dwelling distant from an isolation suite occupied by COVID-19 patient. Assessment of air samples and surface swab samples by rRT-qPCR and cell culture for SARS-CoV-2. Employment of air samplers functioning based on different collection mechanisms. Opportunistic sampling involving the relocation of a volunteer with mild COVID-19 from one state to another.